(untitled) (Itinerarios Educativos, 2021)
This work presents a maths teaching approach at university that holds the main assumption that everyone can learn. This experience was developed in Mathematical Analysis I (AMI), which is a first year course of the Electronic Engineering Degree Program at Universidad Nacional de Moreno in Buenos Aires, Argentina. It is part of an inclusion-oriented research work conducted by collaborative groups of professors and researchers that reflect upon teaching. In fact, the AMI team focused on creating a learning environment that would enable students to share their productions, mistakes, and difficulties as a condition for building mathematical knowledge. Thus trust becomes not only a pillar for developing pedagogical relationships but also a key element to enable knowledge transfer. This work was started in 2019 and has been adjusted to the particularities related to the lockdown caused by the COVID-19 pandemic.